Special Repo Rates. - Duffie, Darrell (Journal of Finance, 1996)
This article provides the causes and symptoms of special repo rates in a competitive market for repurchase agreements. A repo rate is, in effect, an interest rate on loans collateralized by a specific instrument. A 'special' is a repo rate significantly below prevailing market riskless interest rates. This article shows that specials can occur when those owning the collateral are inhibited, whether from legal or institutional requirements or from frictional costs, from supplying collateral into repurchase agreements. Specialness increases the equilibrium price for the underlying instrument by the present value of savings in borrowing costs associated with the repo specials.